A study on the service quality level of Selesa Hotel Seminar package services / Siti Khairaani Nordin - Nordin, Siti Khairaani (2004)
All hotels, at every level, need to recognize that their customers have certain expectations and there is a need to exceed not only the expectations but also satisfactions. Effective strategy to meet the customer expectations can bring a big impact to business. As hospitality and tourism industry in Malaysia are rapidly growing, therefore every members that involve in this area have to know the need and wants of customer to satisfy them. This research done to evaluate the service quality level of Selesa Hotel seminar package services. The service quality is measured based on the degree of satisfactions among customers. This research has used SERVQUAL method that consist of reliability, empathy, tangibles, responsiveness and assurance to evaluate the level of service quality. The conclusion is most of the customer in Selesa Hotel satisfied with the seminar package service provided. At the end, researcher had identified some factors that can be taken consideration to help Selesa Hotel management in Pasir Gudang to improve customer service level.